(untitled) (Latakia University Journal -Engineering Sciences Series, 2016)
دخلت تطبيقات شبكات الحساسات اللاسلكية بشكل واسع في نظم المراقبة الصحية، حيث أسهمت في التطور النوعي لهذه الشبكات بما يؤمن المراقبة الحثيثة على مدار الساعة، مع تحسين جودة هذه المراقبة وتنظيمها. ويرتبط تحسين أداء شبكات الحساسات اللاسلكية الطبية WMSN بتحسين آلية نقل المعطيات الذي يعد من أهم المجالات التي تهتم بها الأبحاث والدراسات في الآونة الأخيرة. ومن هنا تأتي أهمية هذا البحث الذي يهدف إلى دراسة بنى شبكات الحساسات اللاسلكية التي يمكن أن تستخدم في مراقبة الأجنحة في المشافي ومراكز العناية والمراقبة الصحية، واستخلاص التوصيات والاقتراحات الضرورية من أجل اختيار بنية شبكات الحساسات اللاسلكية الطبية المناسبة واقتراح آليات الدخول المناسبة. وذلك من أجل بنى شبكية مختلفة بالحجم. وقد تم ذلك من خلال اقتراح السيناريوهات المناسبة لتطبيقات المراقبة هذه، وإجراء المحاكاة في ظروف عمل مشابهه لعمل الشبكة، بما يؤمن نقل معطيات عقد هذه الشبكة إلى نقطة النفاذ الرئيسية، مع دراسة تأثير بنية الشبكة وطريقة استخدام تقنية نقل المعطيات، وتحديداً استخدام تقنية ZigBee سواء مع تمكين إشارة المنارة أو بدون تمكين إشارة المنارة. حيث تم تقييم التحسن اعتماداً على البارامترات الأساسية في مثل هذه الشبكات مثل النفاذية، والتأخير الزمني، ونسبة التسليم. وقد توصلت الدراسة إلى مجموعة من التوصيات بخصوص حجم الشبكة ونوع البنية المستخدمة وآلية الدخول إلى الوسط. The wireless sensors network applications are widely used in health monitoring systems. In fact, they contribute to the qualitative development of these networks so as to ensure the tireless clock surveillance, and improve and regulate the quality of monitoring. Associated with improving the performance of wireless medical sensor networks WMSN is improving data transfer mechanism which is one of the most important areas of interest to research and study in recent times. Hence the importance of this research lies in the study of the structures of wireless sensor networks that can be used to control the wards in hospitals, health centers and monitoring care. The research also draws necessary recommendations and suggestions for the selection of appropriate medical wireless sensors networks structure and proposees appropriate medium access control mechanism in order to build networks of different sizes. This has been done by proposing appropriate scenarios for surveillance applications to perform simulation that is similar to the working conditions of the networks. This can ensure the transfer of nodes data to the main access point and can give an opportunity to study the impact of network architecture and how to use the data transfer technology, specifically the use of ZigBee technology, both with beacon mode enabled inenabled. Improvement was evaluated based on the basic parameters in such networks, such as throughput, the time delay, and the delivery ratio. The study found a set of recommendations regarding the size of the network, the type of structure and the mechanism used to access medium.